The macroeconomics of TANSTAAFL - Volker Grossmann; Thomas M. Steger; Timo Trimborn (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2011)
This paper shows that dynamic inefficiency can occur in dynamic general equilibrium models with fully optimizing, infinitely-lived households even in a situation with underinvestment. We identify necessary conditions for such a possibility and illustrate it in a standard R&D-based growth model. Calibrating the model to the US, we show that a moderate increase in the R&D subsidy indeed leads to an intertemporal free lunch (i.e., an increase in per capita consumption at all times). Hence, Milton Friedman's conjecture There ain't no such thing as a free lunch (TANSTAAFL) may not apply.
Keywords: E20; H20; O41; 330; intertemporal free lunch; dynamic inefficiency; R&D-based growth; transitional dynamics